ANALISA KEBUTUHAN MEDIA PROMOSI KESEHATAN PADA TUBERKULOSIS LATEN - Yuniar, Isma; Dewi, Yulia Lanti Ratna; Setyowati, Retno; Sugihardjo, Sugihardjo; Darojah, Nurhayati; Supriyanto, Supriyanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Tuberculosis (TB) is one of the world's major health problems. Based on data from the WHO Global TB Report 2024, the country with the second highest tuberculosis rate in the world is Indonesia. Latent Tuberculosis Infection (ILTB). ILTB is a new challenge in the tuberculosis disease control programme. WHO as a world health organisation also recognises that diagnosing and treating ILTB is an important strategy to accelerate the global reduction of tuberculosis to achieve tuberculosis elimination. Evaluation results through interview surveys illustrate that health promotion on latent tuberculosis is still not optimal due to lack of resources. The lack of information and low knowledge of latent tuberculosis infection in the community. This condition requires health promotion with effective media to achieve the target achievements in ILTB. Objective: To analyse the need for health promotion media on latent tuberculosis. Methods: This research is a research with a mix method approach. with a mixed method approach, namely a quantitative approach combined with a qualitative approach. The quantitative approach used a cross sectional design to obtain information on health promotion that has been implemented, The sampling method used total sampling, there were 25 MSI cadres, data collection using questionnaires. Results: The results of the study include quantitative results supported by qualitative results. The quantitative results show that most cadres only occasionally use health promotion media as much as 72%, with the types that have been varied, the most are posters as much as 17%, print media types 53%, content about tuberculosis prevention 31%, with individual health promotion methods such as home visits as much as 84%. while the need for health promotion media on latent tuberculosis was studied using a qualitative approach. Data collection techniques used questionnaires and in-depth interview guides. Data analysis used descriptive analysis and content analysis. The results of the theme found that the media for promoting latent TB health was still minimal and information in the media required complete information. Conclusion: The conclusion of this study is the need for printed latent TB media with complete content so that media can be created that is appropriate to the needs of the community.